(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Climate change is the top most important issue in the modern world. Various aspects of Bangladesh are verily affected by climate change. An agro-climatic study was conducted in Khulna, Satkhira and Bagerhat district in Khulna division as well as the Southwestern coastal part of Bangladesh with last 30 (1981-2011) years of some climatic data of average temperature, maximum temperature, seasonal total rainfall, average humidity and sea level pressure to address the climatic variability and its impacts on Boro rice production in Southwestern coastal part of Bangladesh. The average temperature increased by 0.51°C in Boro season in this area. The sea level pressure was about stable here. The Boro rice production increased by 0.04 and 0.3 tha-1 in Khulna and Bagerhat district. However most of the time the production showed increasing trends except in 2007 and 2009 affected by two devastating natural calamities as SIDR and AILA occurred in these two year respectively. J. Environ. Sci. & Natural Resources, 9(1): 95-98 2016